A surveillance study on dairy farmers selected in Baghabari milk pocket area of Bangladesh (Asian Journal of Medical and Biological Research, 2016)
This study was carried out to reveal the animal agriculture status of the dairy farmers. The survey was conducted by random sampling on 100 dairy farmers (50 from Shahzadpur upazila and 50 from Bera upazila). A pretested questionnaire was developed and multiplied for data collection. The data collected were brought to the headquarters of Bangladesh Livestock Research Institute, Savar, Dhaka for analysis. After analysis it was found that the education level of the farmers of Shahzadpur upazila was better than that of Bera upazila, where 74% farmers of Shahzadpur and 66% farmers of Bera were engaged in agriculture. The average annual income and expense of the farmers of Shahzadpur were greater than that of Bera. The average total land, cultivable land and total livestock population per farmer were also higher in Shahzadpur upazila than in Bera upazila. In case of diversity of different genotypes of dairy cattle, except Jersey cross the number of Pabna, Sindhi cross, Shahiwal cross and H-F cross was much greater in Shahzadpur than in Bera. Most of the farmers purchase concentrate feeds and produce roughages in both the locations, where feed scarcity was seen mostly during rainy season. About 56% farmers treat their cattle with the help of veterinary surgeon and 44% farmers provide treatment with the help of veterinary field assistant in Shahzadpur, while the scenery was almost opposite in Bera. About 90% farmers of Bera upazila and 95% of Shahzadpur upazila used anthelminitics to deworm their animals. Most of the farmers in both sites dewormed their cattle every three months. About 78% farmers of Shahzadpur and 76% of Bera vaccinated their animals. About 85% farmers of Shahzadpur had been found to properly dispose the carcasses, where as only 48% farmers had been found to do it in Bera. Almost all the farmers washed their hands, equipment and udders of the cows with clean water before milking in both Shahzadpur and Bera. Approximately, all the farmers of both the locations milked their cows twice a day, did not perform milk testing and sold the raw fresh milk to the cooperative societies. All farmers used cow dung as fuel. Overall, it was revealed that Shahzadpur upazila was more advanced than Bera upazila in almost all aspects of animal agriculture.Asian J. Med. Biol. Res. March 2016, 2(1): 62-66